Channeling of aminoacyl-tRNA for protein synthesis in vivo. - Negrutskii, B S (1991)
Channeling, the direct transfer of metabolic intermediates from one enzyme to another in a pathway, has received increased attention as an explanation for the high efficiency of cellular processes. The known structural organization of the protein biosynthetic machinery, and a recent suggestion that aminoacyl-tRNAs may be channeled, has led us to devise a direct test of this possibility. By employing the technique of electroporation, conditions were established for the introduction of aminoacyl-tRNAs into Chinese hamster ovary (CHO) cells. We show, by coelectroporation of various combinations of free [14C]amino acids and [3H]aminoacyl-tRNAs, that whereas the free amino acids serve as effective precursors for protein synthesis, the exogenous aminoacyl-tRNAs are utilized poorly, if at all. The lack of incorporation into protein from added aminoacyl-tRNAs is not due to their leakage from the cell, to their instability, or to their damage during electroporation. Furthermore, in contrast to the findings with intact cells, extracts of CHO cells incorporate both free amino acids and aminoacyl-tRNAs into protein with similar efficiencies. Based on these observations, we conclude that the inability of exogenous aminoacyl-tRNAs to serve as precursors for protein synthesis is due to the structural organization of intact cells that leads to channeling of this substrate in vivo. Thus, we propose that endogenously synthesized aminoacyl-tRNA is directly transferred from aminoacyl-tRNA synthetase to elongation factor to ribosome without dissociation into the cell fluid, and as a consequence, usage of exogenously introduced molecules is precluded.